PENGARUH BUDAYA ORGANISASI, MOTIVASI KERJA, KEPEMIMPINAN TRANSFORMATIONAL TERHADAP KOMITMEN ORGANISASIONAL DAN KINERJA KARYAWAN (Studi Pada PT Gunawan Fajar) - Fitria Dwi Febrianti (JURNAL TRANSFORMATIF UNKRISWINA SUMBA, 2024)
This study aims to analyze the organizational culture, work motivation , transformational leadership on organizational commitment and employee performance at PT Gunawan Fajar. The results of the research are expected to be able to help policy makers and strategies of the management of PT Gunawan Fajar so that it can survive in the era of globalization. Proposed hypothesis : organizational culture has a significant effect on organizational commitment, organizational culture has a significant effect on employee performance, work motivation has a significant effect on organizational commitment, work motivation has a significant effect on employee performance, transformational leadership has a significant effect on organizational commitment, transformational leadership has a significant effect on employee performance, organizational has a significant effect on employee performance. Data collectionin research is by survey method. The population used in this study was 65 permanent employees. This study uses a partial least square (PLS) analysis tool. The results is organizational culture, work motivation and transfomatonal leadership has a significant effect on organizational commitment. Organizational culture, transformaional leadership, organizational commitment has a significant effect on employee performance but organizational justice not a significant justice not a significant effect on employee performance.